The significance of trisomy 7 mosaicism in noninvasive prenatal screening - Yiming Qi; Jiexia Yang; Yaping Hou; Fangfang Guo; Haishan Peng; Dongmei Wang; Qianyi Du; Aihua Yin (Human Genomics, 2019)
Abstract Background This study was an evaluation of the role of noninvasive prenatal testing (NIPT) in the detection of trisomy 7 in prenatal diagnosis. Method A total of 35 consecutive cases underwent screening for trisomies by cell-free DNA testing between April 2015 and November 2017 due to suspicious NIPT results; these cases represented 0.11% of patients (35/31,250) with similar frequencies of abnormal results among the laboratories performing the tests. NIPT was offered to further screen for common fetal chromosomal abnormalities. Karyotype analysis, chromosomal microarray analysis (CMA), and next-generation sequencing (NGS) were used to detect 20, 14, and 25 patients, respectively, who accepted confirmatory diagnostic testing. Results High-risk results by NIPT were recorded for trisomy 7 alone in 29 women: dual aneuploidy in 4 patients and multiple aneuploidy in 2 patients. Karyotype analysis of amniotic fluid cells was normal in all 20 pregnancies, suggesting a probability of confined placental mosaicism. Further CMA data were obtained in 14 of the cases mentioned above, and 2 fetuses were detected with positive results with copy number variation. The NGS results suggested that all these samples were placental chimerisms of chromosome 7, except for one sample that was found to be an additional chimerism of chromosome 2, which was also consistent with the NIPT result. Conclusion Our results may be useful for the counseling of pregnant women in the detection of trisomy 7 by NIPT.